Strategi Manipulasi Pelaku Child Grooming di Media Sosial dan Dampaknya pada Remaja: Systematic Review - Rahma Aprilia; Alya Aziza; Diandra Rezkia; Nayla Inez Rachmawati; Nayla Nayla Fazila Maulidina; Januar Ariyanto (LPPM STIKES Marendeng Majene, 2026)
The widespread use of social media among adolescents has contributed to the rise of digital-based crimes, including child grooming. This systematic review aims to examine and synthesize offenders' manipulation strategies and the psychological impacts experienced by victims. Method: Literature was searched across Google Scholar, PubMed, ScienceDirect, and GARUDA databases using the PRISMA protocol and PECO framework. Of 9,707 articles identified, 12 met the inclusion criteria and were analyzed. Result: Out of the twelve articles analyzed, ten met the MMAT quality evaluation criteria, with four of them rated as high-quality literature (five out of five). The synthesis of the findings shows that offenders implement a systematic and gradual strategy, beginning with emotional trust-building, intense attention-giving, victim isolation, and escalating to threats and coercion. Psychological impacts reported include anxiety, depression, trauma, shame, low self-esteem, social withdrawal, sleep disturbances, and relational confusion. Discussion: This review concludes that child grooming is a layered psychological manipulation process with long-term effects on victims' sense of safety and self-worth, highlighting the need for digital literacy education, improved reporting mechanisms, and comprehensive psychological intervention